Analysis of the importance of anatomical landmarks for the placement of orthodontic mini-implants (Research, Society and Development, 2021)
Introduction: Mini-implants represent a great advance in Dentistry to assist in orthodontic treatment, also called micro implants and micro screws are known as temporary anchorage devices. Objectives: To carry out an integrative literature review, based on the analysis of anatomical landmarks, emphasizing the importance of studying anatomy when placing mini-implants. Methodology: This is an integrative literature review of a qualitative nature based on the guiding question: What morphophysiological changes interfere with the success of mini-implants in orthodontic treatments? The database was: National Library of Medicine of the USA (NLM - PubMed), using the following descriptors (MeSHterms): Anatomy; Mini-implants. Inclusion criteria were published in English, Portuguese and Spanish; publications between January 2000 and January 2021 and that addressed the subject in a satisfactory manner. Articles that do not meet the inclusion criteria were excluded. A total of 198 works were found in full; of these, 3 articles were duplicated in the search strategies, thus totaling 8 selected. Results and Discussion: It was found that it is necessary to analyze the morphophysiological changes that can be found with the use of mini-implants. It was also observed that the size of mini-implants influences the increase in mechanical anchorage, as well as the incidence of the paranasal sinuses, concluding that the main determining factors in bone anchorage are bone density and placement depth. The use of mini-implants in the palate does not interfere with tooth movement, in addition to having enough bone, enabling the insertion of the mini-implant. The authors also report that there are multiple reasons for a mini-implant failure or complete loss, such as periodontitis and peri-implantitis, causing soft and hard tissue infection, especially when inadequate oral hygiene or poor post-surgical control persists. Final considerations: The knowledge and mastery of the anatomical structures of the head and neck, as well as the morphophysiological changes can lead to the implantation of orthodontic mini-implants, contributes to the achievement of clinical success, reducing side effects and the treatment time is reduced.